Monetary Policy with Negative Interest Rates : Decoupling Cash from Electronic Money - Assenmacher, Katrin (IMF Working Papers; Working Paper ;, 2018)
Monetary policy space remains constrained by the lower bound in many countries, limiting the policy options available to address future deflationary shocks. The existence of cash prevents central banks from cutting interest rates much below zero. In this paper, we consider the practical feasibility of recent proposals for decoupling cash from electronic money to achieve a negative yield on cash which would remove the lower bound constraint on monetary policy. We discuss how central banks could design and operate such a system, and raise some unanswered questions.